The genus Anomalon Panzer (Hymenoptera: Ichneumonidae: Anomaloninae) of Iran, with description of a new species - Zardouei Heydari, Maryam; Rakhshani, Ehsan; Mokhtari, Azizollah; Schwarz, Martin (European Journal of Taxonomy, 2020)
The Iranian species of the genus Anomalon Panzer, 1804 (Hymenoptera: Ichneumonidae: Anomaloninae) are reviewed. Four species, Anomalon amseli (Hedwig, 1961), A. chinense (Kokujev, 1915), A. cruentatum (Geoffroy, 1785) and A. narinae Zardouei & Rakhshani sp. nov., are found to occur in Iran. The female of A. amseli is described for the first time. Anomalon chinense is a new record for Iran. A key to the known Anomalon species of Iran is provided.